Blood pressure‐lowering effects of GLP‐1 receptor agonists exenatide and liraglutide: a meta‐analysis of clinical trials. Issue 8 (20th March 2013) - Wang, B.; Zhong, J.; Lin, H.; Zhao, Z.; Yan, Z.; He, H.; Ni, Y.; Liu, D.; Zhu, Z.
<x xml:space="preserve">Abstract</x> Aims Aside from lowering blood glucose, glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) attract much attention because of their cardioprotective effects. The aim of this study was to assess the blood pressure‐lowering effects of the GLP‐1 RAs exenatide and liraglutide compared with other common drugs used to treat type 2 diabetes (T2DM) based on randomized controlled trials (RCTs) including data describing complete blood pressure (BP) changes from baseline. Methods We searched the major databases for published or unpublished RCTs that had been performed in patients with T2DM and compared the effects of exenatide and liraglutide to those of other common drugs used to treat T2DM. The RCTs that included data describing BP changes between the baseline and the end of the study were selected for further analysis. Results A total of 16 RCTs that enrolled 3443 patients in the GLP‐1 RA treatment group and 2417 subjects in the control group were included in this meta‐analysis. The GLP‐1 RA exenatide reduced systolic blood pressure (SBP) when compared with both placebo and insulin glargine, with mean differences of −5.24 and −3.46 mmHg, respectively, and with 95% confidence intervals (CI) of −6.88 to −3.59, p < 0.00001 and −3.63 to −3.29, p < 0.00001, respectively. Meanwhile, in the exenatide‐treated group, diastolic blood pressure (DBP) was reduced by −5.91 mmHg, with a 95% CI of −7.53 to −4.28, p < 0.00001 compared with the placebo group, and −0.99 mmHg with a 95% CI of −1.12 to −0.87, p < 0.00001 compared with the sitagliptin group. SBP changes in this meta‐analysis were assessed in the groups treated with 1.2 or 1.8 mg liraglutide per day. In the 1.2 mg‐treated group, liraglutide treatment reduced SBP compared with placebo and glimepiride treatment, with mean differences of −5.60 and −2.38 mmHg, and 95% CIs of −5.84 to −5.36, p < 0.00001 and −4.75 to −0.01, p = 0.05, respectively. In the 1.8‐mg‐treated group, liraglutide also reduced SBP compared with placebo and glimepiride treatment with mean differences of −4.49 and −2.62 mmHg, and a 95% CI of −4.73 to −4.26, p < 0.00001, and −2.91 to −2.33, p < 0.00001, respectively. Conclusion Treatment with the GLP‐1 RAs exenatide and liraglutide reduced SBP and DBP by 1 to 5 mmHg compared with some other anti‐diabetic drugs including insulin, glimepiride and placebo for patients with T2DM. GLP‐1 RAs may offer an alternative therapy for these patients and will help provide extra cardiovascular benefits.